Down to earth archaeology - Adams, William Y. 1927-2019, (Sudan Archaeological Research Society publication ;, 2022)
Professor William Y. Adams presents sixteen papers on Nubia, written at various times during his lengthy and productive academic career. Most of those selected had been previously published only in a limited way; encompassing a wide range of topics, Adams wanted to enable them to reach a wider readership than they had originally.